Pengaruh Penerapan Media Asesmen Formatif Berbasis Quizizz Paper Mode Terhadap Motivasi Belajar Peserta Didik Pada Pelajaran PAI BP - Sri Santo, Muhamad Raihan; Hermawan, Iwan; Aini Farida, Nur (Universitas Majalengka, 2024)
This research aims to determine the effect of implementing formative assessment media based on Quizizz Paper Mode on the learning motivation of class VII students at SMPIT Al-Ridwan, Karawang Regency. This study uses a quantitative approach. The method used in this research is a Quasi Experiment type experimental method with a Nonequivalent Control Group Design. The results of this research are: 1) The implementation of formative assessment media based on Quizizz Paper Mode in class VII Ikhwan SMPIT Al Ridwan Karawang Regency went very well. This can be seen from the increase in students' understanding and response to the observation results. 2) There is an increase in students' learning motivation in PAIBP subjects in class VII SMPIT Al Ridwan. It can be seen from the average pretest and posttest for the experimental class that there was an increase of 3.77. 3) The T-test result is 0.008 < 0.05, which means H0 is rejected and Ha is accepted. So it can be concluded that there is a significant influence on the application of Quizizz Paper Mode-based formative assessment media on students' learning motivation in PAIBP subjects in Class VII SMPIT Al Ridwan, Karawang Regency.